People with limiting long-term conditions report poorer experiences and more problems with hospital care. - Hewitson, P; Skew, A; Graham, C; Jenkinson, C; Coulter, A (BioMed Central, 2014)
BACKGROUND: Long-term conditions have a significant impact on individuals, their families, and the health service. As people with these conditions represent a high proportion of hospital admissions, investigating their experiences of inpatient care has become an important area of investigation. We conducted a secondary analysis of the NHS adult inpatient survey for England to compare the hospital experiences of three groups of patients: those without long-term conditions, those with a single long-term condition, and those with multiple long-term conditions. We were particularly interested in the extent to which these patients received self-management support from hospital staff, so we developed a brief summary tool drawn from salient questions in the survey to aid the comparison. METHODS: Analysis of data from the 2011 national adult inpatient survey (n = 65,134) to compare the experiences of three groups of patients: those with no limiting long-term conditions (No-LLTC), those with one limiting long-term condition (S-LLTC), and those with two or more limiting long-term conditions (M-LLTC). The main outcome measure was patients' self-reports of their experience of inpatient care, including staff-patient interactions, information provision, involvement in decisions and support for self-care and overall ratings of care. A short form scale, the Oxford Patient Involvement and Experience scale (OxPIE) was developed from the adult inpatient survey and used to compare the groups using logistic regression. RESULTS: There were significant differences between the No-LLTC group in comparison to both the S-LLTC and M-LLTC groups. Patients with limiting long-term conditions reported significantly worse hospital experiences than those without, as measured by OxPIE: S-LLTC odds ratio = 1.23, 95% CI 1.03-1.48; M-LLTC odds ratio = 1.64, 95% CI 1.19-2.26. Responses to a single global rating question were more positive but not strongly correlated with OxPIE. CONCLUSIONS: Patients with LLTCs were more critical of their inpatient care than those with no LLTCs. Those with more than one long-term condition reported worse experiences than those with a single limiting condition. Simple rating questions may not be sufficiently sensitive to reflect important aspects of patients' experience.